New Approach for Managing Keys in Cloud & Use Cases for Cloud Computing - Singh, Sarvesh; Shukla, Anupam; Sharma, Ankit; Lone, Kalimullah (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Now a days cloud computing is best innovative technology in the field of IT. In its broadest usage, the term cloud computing refers to the delivery of IT resources over the internet as opposed to hosting and operating these resources locally, such as a college or university network. These resources can include application and services as well as infrastructure and services over the network. Any organization can purchase these resources on as needed basis and avoid the capital expenditure cost of software and hardware. Security is major problem in cloud computing, thus key distribution is important thing for managing security in cloud computing. In this paper we derived a proposed algorithms for managing keys in the cloud and also discuss uses cases for cloud computing.